Do Responsible Consumption and Production and Climate Policies Influence an Individual’s Environmentally Oriented Consumption and Anti-consumption? - Felipe Roberto da Silva; Felipe Gerhard (RAC: Revista de Administração Contemporânea)
Objective: this study aims to examine whether the macro and individual contexts can alter the behavioral dynamics of environmentally oriented consumption and anti-consumption. Theoretical approach: the study emphasizes the role of the interaction between institutional factors and personal perceptions – mediated by social and cultural networks – in promoting sustainable practices. Method: multilevel modeling was used to analyze both individual and country-level effects using data from over 24,000 individuals across 25 European countries. Results: the findings reveal that supportive macro conditions and stronger individual concern for climate change increase the likelihood of environmentally responsible consumption. As basic conditions to sustainable development and climate change mitigation are met, individuals are more likely to adopt behaviors that respect planetary limits. Conclusion: this research contributes to the literature on sustainability by quantitatively integrating both contextual levels – an approach that is still uncommon – and by demonstrating how individual perceptions and broader political and cultural environments jointly shape sustainable consumer behavior. The results provide valuable information for public policies that aim to achieve climate goals and advance the Sustainable Development Goals (SDGs).